A Vision on Intelligent Medical Service for Emergency on 5G and 6G Communication Era - Nayak, Sabuzima; Patgiri, Ripon (EAI Endorsed Transactions on Internet of Things, 2020)
Emergency service is the most important research field for welfare of human kind. Some examples are ambulances and fire control truck. However, these conventional emergency services are not equipped with appropriate equipment to provide high QoS. For instance, conventional medical emergency services include ambulances with drivers and oxygen supplies only. Another example is the conventional fire control systems that only include fire control truck, which is not suitable for current scenario due to various challenges, for instance, road traffic. In addition, accidental services are unsatisfactory in current and future emergency services. Emergency service is required by anyone at anytime and anywhere. Therefore, it is the time to redefine and restructure the conventional emergency service for saving more lives. Due to the advent of wireless communication technology, it is possible to provide the emergency service on the spot in nearly real-time to save lives. Moreover, integration of Artificial Intelligence with smart devices can change the definition of emergency services. In this chapter, we envision the various emergency services to advance the healthcare services. Besides, we envision the impact of emergency services on healthcare with the help of Artificial Intelligence, 5G and 6G communication technology.
Keywords: Emergency Service; Healthcare; 5G Communications; 6G Communications; Wireless Communications; Internet of Things; Internet of Everything; Vehicular Technology; Drones; Mobile Hospital; Hospital-to-Home Services; Fire Control; Accidental Services; Natural Disaster